Dombi Interval Valued Neutrosophic Graph and its Role in Traffic Control Management - D. Nagarajan; M.Lathamaheswari; S. Broumi; J. Kavikumar (Neutrosophic Sets and Systems, 2019)
An advantage of dealing indeterminacy is possible only with Neutrosophic Sets. Graph theory plays a vital role in the field of networking. If uncertainty exist in the set of vertices and edge then that can be dealt by fuzzy graphs in any application and using Neutrosophic Graph uncertainty of the problems can be completely dealt with the concept of indeterminacy.